Approaches to fostering entrepreneurial excellence in Malaysian universities - Ab Wahid1, Hariyaty; Mahmood, Ahmad; Mohd Ariffin, Siti Zubaidah; Abdul Rahman, Rafiduraida; Wan Mustaffa5, Wan Salmuni (Journal of Islamic, Social, Economics and Development, 2025)
Entrepreneurship encompasses generating value by developing products and services that positively impact both the economy and society. This process requires the design, management, and operation of a venture. Globally, governments, legislators, planners, and various stakeholders have increasingly emphasized the importance of entrepreneurship. In Malaysia, this significance is reflected in the strong support for entrepreneurship across all educational levels, including higher education institutions. Entrepreneurship is recognized as a critical soft skill that can be developed through higher education. It serves as the foundation for cultivating an entrepreneurial mindset as a way of thinking that enables successful entrepreneurs to achieve their goals by viewing challenges, mistakes, and failures as opportunities for growth and success. Therefore, this conceptual article aims to highlight the effective methods for teaching and fostering an entrepreneurial mindset on university campuses. This will equip students with the ability to realize their aspirations by being observant of their environment, solving problems with an entrepreneurial approach, and demonstrating high levels of motivation, decisiveness, and accountability in their entrepreneurial pursuits. To nurture the entrepreneurial mindset, universities must create learning experiences that promote entrepreneurship within classrooms, campus environments, organizations, and communities. Additionally, for these initiatives to succeed, entrepreneurship instructors must be well-equipped with the necessary entrepreneurial skills and experiences. As a result, the solutions provided should empower students to think entrepreneurially in various domains, including management, academic programs, real-world engagement with entrepreneurs, and collaboration with entrepreneurship agencies. Thus, this paper aims to explain the entrepreneurial mindset and the challenges associated with integrating it into Malaysian campuses. The recommendations provided will benefit universities, campus residents, entrepreneurship lecturers, and all those interested in fostering entrepreneurial thinking within the campus ecosystem.